2013
DOI: 10.1021/am3031745
|View full text |Cite
|
Sign up to set email alerts
|

Photoactive Porous Silicon Nanopowder

Abstract: Bulk processing of porous silicon nanoparticles (nSi) of 50-300 nm size and surface area of 25-230 m(2)/g has been developed using a combustion synthesis method. nSi exhibits consistent photoresponse to AM 1.5 simulated solar excitation. In confirmation of photoactivity, the films of nSi exhibit prompt bleaching following femtosecond laser pulse excitation resulting from the photoinduced charge separation. Photocurrent generation observed upon AM 1.5 excitation of these films in a photoelectrochemical cell sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The photoactivity of nanoporous silicon in separating the photoexcited e -/h + pairs has been verified, while the promising uses of the sensitive photo-responsivity in solar water splitting, visible light-driven photodegradation of methyl orange, phenol, nitroaromatics have also been broadly discussed. [25][26][27][28] However, the specific surface area (SSA) is often in the range of 25-300 m 2 •g - 1 . Inspired by a recent finding that significant SSA up to 864 and 1125 m 2 •g -1 has been realized for the first time on p-type porous silicon by electrochemical etching, 29,30 mesoporous silicon with large surface area has thus been investigated in this study.…”
Section: 24mentioning
confidence: 99%
“…The photoactivity of nanoporous silicon in separating the photoexcited e -/h + pairs has been verified, while the promising uses of the sensitive photo-responsivity in solar water splitting, visible light-driven photodegradation of methyl orange, phenol, nitroaromatics have also been broadly discussed. [25][26][27][28] However, the specific surface area (SSA) is often in the range of 25-300 m 2 •g - 1 . Inspired by a recent finding that significant SSA up to 864 and 1125 m 2 •g -1 has been realized for the first time on p-type porous silicon by electrochemical etching, 29,30 mesoporous silicon with large surface area has thus been investigated in this study.…”
Section: 24mentioning
confidence: 99%
“…Examination of the literature (Bao et al 2007;Richman et al 2008;Hai et al 2009;Ibisate et al 2009;Won et al 2009Won et al , 2011Yu et al 2010;Zhu et al 2010Yermekova et al 2010;Chen et al 2011aChen et al , b, 2012aChen et al , b, 2013a Gallego-Gomez et al 2011;Gao et al 2011;Guo et al 2011;Jia et al 2011;Lu et al 2011;Pallavidino et al 2011;Zhang and Huang 2011;Batchelor et al 2012;Fang et al 2012;Shen et al 2012Shen et al , 2013Tao et al 2012a, b;Wang et al 2012;Yoo et al 2012;Huachao et al 2013;Jung et al 2013;Du et al 2013;Hong et al 2013;Jiang et al 2013;Lee et al 2013;Liu et al 2013;Luo et al 2013;Ma et al 2013;Meekins et al 2013;Wen et al 2013;Xing et al 2013a, b;Yoo et al 2013;Yu et al 2013;Yue et al 2013;Xia et al 2014) reveals that all three classes of porosity (see handbook chapters on ▶ Macroporous Silicon, ▶ Mesoporous Silicon, and ▶ Microporous Silicon) are achievable with magnesiothermic reduction, as are extremely high surface area structur...…”
Section: Merits Of Magnesiothermic Reductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Silicon dioxides can be obtained from natural resources [15][16][17][18][19][20] or by synthesis through various techniques, including the sol-gel and polymer-template methods. [21][22][23][24][25][26][27][28][29][30][31] For the porous silicon prepared from porous silicon dioxides, one of the most attractive uses is as anode materials for lithium-ion batteries. [17][18][19]28,[32][33][34][35][36] We previously reported that we could obtain silicon from pulverized porous silica glass samples, which in turn were prepared from sodium borosilicate glass samples by the heat treatment for phase separation and acid leaching of the borate-rich phase.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, various types of silicon dioxides with nanometer‐size structures have been successfully converted to silicon retaining morphologies similar to those of the original silicon dioxides 12–28 . Silicon dioxides can be obtained from natural resources 15–20 or by synthesis through various techniques, including the sol‐gel and polymer‐template methods 21–31 . For the porous silicon prepared from porous silicon dioxides, one of the most attractive uses is as anode materials for lithium‐ion batteries 17–19,28,32–36 …”
Section: Introductionmentioning
confidence: 99%